Mental Health of COVID-19 Survivors at 6 and 12 Months Postdiagnosis: A Cohort Study - Huang, Xin; Liu, Lin; Eli, Buzohre; Wang, Jingyi; Chen, Yaru; Liu, Zhengkui (Frontiers in Psychiatry, 2022)
Objective: As COVID-19 persists around the world, it is necessary to explore the long-term mental health effects in COVID-19 survivors. In this study, we investigated the mental health outcomes of survivors of COVID-19 at 6 and 12 months postdiagnosis. Methods: Posttraumatic stress disorder (PCL-5), depression (PHQ-9), anxiety (GAD-7), resilience (CD-RISC-10), perceived social support (PSSS), personality traits (CBF-PI-15) and sociodemographic information were examined among 511 survivors of COVID-19 (48.1%, females; Mage = 56.23 years at first assessment) at 6 and 12 months postdiagnosis. The data were analyzed with Wilcoxon signed rank tests and multivariable logistic regression models. Results: The prevalence of anxiety, depression, and PTSD at 6 and 12 months after diagnosis was 13.31% and 6.26%, 20.35% and 11.94%, and 13.11% and 6.07%, respectively. The risk factors for all symptoms were as follows: higher neuroticism; lower openness, extraversion, agreeableness, and resilience; greater life disruptions due to COVID-19; poorer living standards; and increased symptoms of PTSD or depression at 6 months postdiagnosis. Conclusions: The mental health of COVID-19 survivors improved between 6 and 12 months postdiagnosis. Mental health workers should pay long-term attention to this group, especially to survivors with risk factors.